2003
DOI: 10.1111/1540-6210.00262
|View full text |Cite
|
Sign up to set email alerts
|

Learning Organizations in the Public Sector? A Study of Police Agencies Employing Information and Technology to Advance Knowledge

Abstract: In an attempt to reap the purported benefits that "knowledge workers" bring to organizations, many police departments have shifted to a community problem-oriented policing philosophy. Rather than focusing on enforcement and incarceration, this philosophy is based on the dissemination of information to promote a proactive, preventative approach to reduce crime and disorder. In keeping with much of the contemporary literature on the "learning organization" (sometimes called the "knowledge organization"), police … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(107 citation statements)
references
References 30 publications
1
89
0
6
Order By: Relevance
“…Similarly, a research survey by Chan (2001: 156) of 506 Australian police officers identified that 72 per cent felt that information technology had made a great difference to police work and provided 'the capacity to follow a more problem-oriented style of policing'. Brown and Brudney (2003) concur that the effects of IT are favourable with regards to enabling benefits of a learning organisation, such as improving policing problem-solving abilities.…”
Section: The Requirement For Mobile Technology In Policingmentioning
confidence: 66%
“…Similarly, a research survey by Chan (2001: 156) of 506 Australian police officers identified that 72 per cent felt that information technology had made a great difference to police work and provided 'the capacity to follow a more problem-oriented style of policing'. Brown and Brudney (2003) concur that the effects of IT are favourable with regards to enabling benefits of a learning organisation, such as improving policing problem-solving abilities.…”
Section: The Requirement For Mobile Technology In Policingmentioning
confidence: 66%
“…Current body of literature suggests that the LO serves as a mechanism that influences an organization's performance through enhanced organizational effectiveness [4], [22], [41] and [1].…”
Section: Introductionmentioning
confidence: 99%
“…LGAs and other government organisations vertically and horizontally (Brown and Brudney, 2003). Technical issues related to e-Government are no exception and several research studies are satiated with evidences (Janssen and Cresswell, 2005;Kamal et al, 2009).…”
Section: Local Government and The Decision-making Contextmentioning
confidence: 99%
“…Yildiz (2007) asserts that this complicates the planning and decision-making processes in LGAs. Brown and Brudney (2003) report that such attitudinal perceptions of government decision makers also constrain these processes. However, a better investigation and understanding of the attitudinal and other behavioural factors (including the decision and organisational context) influencing the decision-making process for IT adoption might help in making the complexity more manageable.…”
Section: Local Government and The Decision-making Contextmentioning
confidence: 99%